Framework for a learning management system at a university of technology with a weak information technology maturity system - Machika, P.C.; Dolley, F. (South African Journal of Higher Education, 2018)
In the past, adoption of the learning management system (LMS) has been voluntary with a limited amount of training at the micro level within a particular university of technology.  From discussions with academic staff it emerged that across the entire institution approximately 10-15% of academic staff used a particular LMS with only about 5% actively engaged. As the particular university progresses its broader plans for teaching and learning enhanced by technology, the LMS will become increasingly important as a tool to help realise the university’s goals. The aim of the article is to gain a clear understanding of the potential barriers and obstacles encountered when implementing an LMS at a macro and meso level where the information technology system is weak. The article includes a discussion on a framework in support of the development of the LMS at a macro and meso level within a university of technology.